Punctoplasty surgery combined with 22-gauge intracath intubation in punctal stenosis: A practical, cost-effective, and efficient method (Annals of Medical Research, 2025)
Aim: To evaluate the outcomes of cases with epiphora due to punctal stenosis, in which intubation was performed using a 22-gauge (G) intracath in combination with the two-snip or three-snip technique.Materials and Methods: The study included 45 eyes of 23 patients with punctal stenosis who presented to our clinic with epiphora. The severity of punctal stenosis in all cases was graded according to the Kashkouli classification; 32 eyes (71.1%) were graded as grade 1, and 13 eyes (28.9%) as grade 2. Epiphora was confirmed using the fluorescein disappearance test. Lacrimal system lavage was performed in all cases to evaluate the distal lacrimal system, and distal passage patency was observed. Cases were considered successful if they had a Munk score of 0 or 1 and a fluorescein disappearance test score of 0.Results: The study included 10 male and 13 female patients, with a mean age of 62.09 ± 12.41 years. The mean follow-up period was 6.3 ± 4.56 months. Preoperatively, all cases had a Munk score of 4 and a fluorescein disappearance test score of 3. At the final follow-up, no epiphora was observed in 36 eyes (80%), while intermittent epiphora with a Munk score of 2 was reported in 9 eyes (20%). In four eyes with intermittent epiphora, the lavage time exceeded 5 seconds, and in two eyes (one patient), ocular surface disorder due to previous trauma was present. Revision surgery was required in five eyes due to restenosis. Conjunctival reaction developed in six eyes (three patients).Conclusion: Punctoplasty surgery is an effective option in cases with punctal stenosis. The method we used is effective and cost-efficient in terms of punctal intubation, and it may serve as an alternative to silicone tube intubation.
Keywords: Lacrimal punctum; Nasolacrimal apparatus; Epiphora; Punctal stenosis